Conceptualizing essential components affecting health tourism satisfaction in Asia: Does context matter? - Sarker, Moniruzzaman *; Nafisa, K.; Wong, Brian K. M.; Moghavvemi, S. (Routledge, 2021)
Asian countries, specifically Thailand, Singapore, Malaysia, and India, are documented as the preferred health tourism destinations among healthcare travelers. Despite the significant increase in global revenue over the last fifteen years, there is still a lack of comprehensive understanding about the factor affecting health tourist satisfaction in this region. Using the critical literature review technique, this study suggests that the commonly adopted SERVQUAL dimensions do not cover the overall aspects of health tourism satisfaction. Instead, we propose seven key attributes of healthcare service and four attributes of tourism destination. Although conceptual components of the proposed framework are not contextually driven, empirical findings may vary due to the standard of service provisions across health tourism destinations. The proposed model will also mitigate the managerial difficulties in designing an appropriate health tourism service.